KEANEKARAGAMAN MIKROALGA DI SUNGAI KATI LUBUKLINGGAU - Harmoko Harmoko; Sepriyaningsih Sepriyaningsih (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
We conducted an initial survey of the microalgal diversity of Kati River located in the City of Lubuklinggau, South Sumatra Province, on March to May 2017. This study aimed to determine the microalgal diversity of Kati River as a baseline data. This study found 47 microalgal species belonging to 42 genera and 27 orders. We found the member of Chlorophyceae and Bacillariophyceae were the most abundant microalgae. We also compared the diversity of Kati River to two other rivers in Lubuklinggai, Mesat River, and Kalingi River. The microalgal diversity of Kati River is higher than Mesat River but lower if compared to Kalingi River. The physicochemical factors of Kati River waters were also measured, the average water temperature was 27°C, average pH was 6.7, and average water transparency was 57 cm. This study found that those environmental factors influenced microalgal diversity in Lubuklinggau rivers, Kati River, as well as Mesat River and Kalingi Rivers, have indicated the same results.